POSITIVISM-POSTPOSITIVISM DEBATE IN SOCIAL SCIENCES - Nekrašas, Evaldas (Politologija, 2015)
The article explores positivism-postpositivism debate in social sciences that has been lasting already for many years. The author does not suppose this debate will end soon since it raises fundamental questions concerning the aims, tasks and methods of social sciences. Though representatives of these sciences differ significantly in views on these questions, the most of them and, in particular, evident majority of representatives of political science virtually holds positivist views. Such questions, which may be called conceptual, are essentially disputable, so they can not be resolved by any empirical research. When examining positivism-postpositivism debate the author singles out, paying tribute to tradition, three aspects of debate: (1) ontological, (2) epistemological, and (3) methodological. Yet he presents the arguments to support his claim that because of its antimetaphysical character positivism can have no ontology at all. Therefore an ontological dispute between positivists and postpositivists is simply impossible. Postpositivists, in discussing epistemological questions, would be inclined to reject positivist viewpoint that our statements and theories about social life can be true (though according to modern positivists, we can never know it for sure). They also would reject the positivist distinction between facts and values, which likewise can be considered as epistemological. But the most serious dispute that is taking place in social sciences concerns methodological questions. The author, in analyzing it, pays most attention to two most influential forms of postpositivism, namely to critical theory and postmodernism. Having discussed genealogy and deconstruction which, though with serious reservations, may be considered as postpositivist methods, the author claims that postpositivism lacks the main part of methodology, i.e. rules of accepting scientific statements and theories. And that is why postpositivism can not win the methodological debate over positivism which has such rules.